Elevated iron status and risk of gestational diabetes mellitus: A systematic review and meta‐analysis. Issue 4 (14th December 2016) - Fernández‐Cao, José C.; Aranda, Núria; Ribot, Blanca; Tous, Mònica; Arija, Victoria
Abstract: The aim of this systematic review and meta‐analysis of observational studies was to assess the relationship between elevated iron status, measured as hemoglobin and ferritin levels, and the risk of gestational diabetes mellitus (GDM). The present study was recorded in PROSPERO (2013:CRD42013005717). The selected studies were identified through a systematic review of scientific literature published in The Cochrane Library and PubMed/MEDLINE databases from their inception until March 10, 2016, in addition to citation tracking and hand‐searches. The search strategy of original articles combined several terms for hemoglobin, ferritin, pregnancy, and GDM. OR and 95% CI of the selected studies were used to identify associations between hemoglobin and/or ferritin levels with the risk of GDM. Summary estimates were calculated by combining inverse‐variance using fixed‐effects model. 2468 abstracts were initially found during the search. Of these, 11 with hemoglobin and/or ferritin data were selected for the meta‐analyses. We observed that high hemoglobin (OR = 1.52; 95% CI: 1.23–1.88), as well as ferritin (OR = 2.09; 95% CI: 1.48–2.96) levels were linked to an increased risk of GDM. Low heterogeneity was observed in hemoglobin (I 2  = 33.3%, P  = 0.151) and ferritin (I 2  = 0.7%, P  = 0.418) meta‐analyses, respectively. Publication bias was not appreciated. High hemoglobin or ferritin levels increase the risk of GDM by more than 50% and more than double, respectively, in the first and third trimester. Therefore, determining of hemoglobin or ferritin concentration in early pregnancy might be a useful tool for recognizing pregnant women at risk of GDM.